State and ritual in a Marxist-Leninist society: East Berlin, 1951 - O'Neil, D; Daniel Patrick O'Neil (2015)
This dissertation examines the relationship between state, ritual, and Stalinism in the context of the Soviet occupation of Germany after 1945, the establishment of the German Democratic Republic, and finally the World Festival of Youth and Students (Weltfestspiele) held in East Berlin in 1951. On the connection between these three phenomena, I take an anti-Durkheimian stance, asserting that ritual, far from being merely epiphenomenal to 'society' or 'the state', is in fact constitutive of them. It is the contention of this thesis that the entity known as 'the state', despite the capacity of some of its organs to project massive physical force, is in ontological term an amorphous, fragile thing. It is a further contention of this thesis that mass public ritual is one of the cornerstones of the ideological work of the state. I argue that the emphasis that the East German state placed on mass ritual was a function of its political and social insecurity. I propose that the German Democratic Republic's fixation on mass displays of unity during the first years of its existence were a function of its insecurity. In 1951, the year in which the Weltfestspiele took place, the German Democratic Republic was barely two years old and was uncertain of its future, wary of both the decidedly limited enthusiasm Germans had displayed for Soviet-backed Marxism-Leninism and the plans its allies in Moscow had for the future of a divided Germany. The East German authorities accordingly set a great deal of store by mass displays of the unity and enthusiasm of 'the people'-yet at the same time, these mass rituals ultimately became carnivals of the regime's insecurity, and demonstrations of its failure to secure authentic political legitimacy amongst its population.